Interplay between tumor cells and immune cells of the colorectal cancer tumor microenvironment: Wnt/β-catenin pathway - Janeeh, Aisha Saleh; Bajbouj, Khuloud; Rah, Bilal; Abu-Gharbieh, Eman; Hamad, Mawieh (Frontiers in Immunology, 2025)
Colorectal cancer (CRC) is currently ranked as the third most frequent human cancer and the fourth leading cause of cancer-related deaths worldwide. Macrophages and immune cell subsets infiltrate the tumor microenvironment (TME) and modulate several cellular events and metabolic processes in CRC. Therefore, CRC-TME-infilitrating macrophages are thought to play a significant role in CRC progression, and could hence be potential therapeutic targets in CRC. Several lines of evidence suggest that the Wingless/Integrated (WNTs) family of signaling proteins plays a crucial role in CRC development and progression. Numerous studies have established that Wnt pathway signaling is involved in CRC-TME interaction; CRC-immune cell interaction in particular. Mounting experimental evidence point to the possibility that the TME in CRC can reciprocally modulate the Wnt/β-catenin pathway. Lastly, several studies have elaborated on the effect of drugs that disrupt the Wnt/β-catenin pathway as means of hindering CRC growth and progression. In this review, we discuss the multifaceted role of Wnt/β-catenin pathway in CRC and its TME as well as CRC-TME interactions. We also elaborate on the potential therapeutic utility of Wnt/β-catenin pathway-related targets in CRC.